التعذيب في الجزائر خلال الثورة التحريرية الولاية الرابعة انموذجا ( 1945م-1962م ) - شمة مسعودة; د/ بوقرين عيسى (جامعة عمار ثليجي الاغواط, 2024)
الجزائري وراء القضبان، سواء كانت معتقلات أو سجون، وأطلق عليها تسمية "مراكز الموت البطيء". تضمنت هذه المراكز مراكز سرية وأخرى رسمية، حيث تقننت في التعذيب شخصيات فرنسية منها الجنرال بيجار، الجنرال أوساريس، والجنرال ماسو. وما زال التعذيب يشهد على أجساد وقصص مجاهدين لا زالوا على قيد الحياة. وكانت من وراء هذه الجرائم مواقف فرنسية، جزائرية، ودولية، وكل منها كان يهدف إلى تحقيق أهداف معينة. وعليه، فإن جرائم فرنسا البشعة التي سجلها التاريخ ضد الجزائر سوف تبقى صفحة سوداء في تاريخ المجتمعات الغربية الأوروبية وخاصة المجتمع الفرنسي. ولذلك، فعلى الأجيال القادمة أن لا تنسى التضحيات التي قدمها الشهداء، وبفضلهم أصبح العلم يرفرف في سماء الجزائر المستقلة. Abstract: This study focuses on the crimes committed by French authorities in the Fourth Wilaya. Torture is a military technique that the French colonialists diligently developed to suppress the revolution, employing specialized agencies for the interrogation of the Algerian people behind bars, whether in detention centers or prisons, which were referred to as "slow death centers." These centers included both secret and official ones. Torture was institutionalized by French figures such as General Bigeard, General Aussaresses, and General Massu. The lasting marks of torture can still be seen on the bodies and in the stories of living freedom fighters. These crimes prompted reactions from French, Algerian, and international parties, each aiming to achieve specific objectives. Therefore, the heinous crimes committed by France, recorded in history against the Algerian people, will remain a dark chapter in the history of Western European societies, especially the French society. It is crucial for future generations to remember the sacrifices made by the martyrs, thanks to whom the flag now flies over an independent Algeria.